PARTICIPATION OF AN ADVOCATE AS A MEDIATOR IN THE RESOLUTION OF FAMILY DISPUTES: NATIONAL AND FOREIGN EXPERIENCE (World Bulletin of Management and Law, 2024)
The article discusses the foreign experience of conducting the mediation procedure in resolving family disputes and conflicts, analyzes the requirements that apply to mediators in foreign countries. It is emphasized that the introduction of mediation is a natural trend of the present time, a way to resolve conflicts in the family sphere, allowing you to get the result that suits the parties to the dispute the most. The settlement of family conflicts is a responsible task, therefore, in most foreign countries, special requirements are imposed on the mediator regarding professional qualifications, additional special education on the profile of family mediation, age, practical experience. However, in addition to the requirements for professional skills and skills of the mediator, there is also a list of requirements for the moral qualities of the mediator. It is concluded that in most developed countries of the world, activities. The mediator is regulated by law and is carried out both on a professional and non-professional basis, however, in a number of countries, the legislation of subjects may establish additional requirements for the mediator. At the same time, as in Uzbekistan, professional mediators are most often persons with higher education or who have received additional professional education on the application of the mediation procedure..
Keywords: Mediation; family dispute; family mediation